The State of Information Literacy in Selected Private Secondary Schools in Dar es Salaam Region, Tanzania - Maro, Zainabu H; Nawe, Julita (University of Dar es Salaam Library Journal, 2019)
This study examined the state of information literacy (IL) in selected private secondary schools in Dar es Salaam, Tanzania by looking at the availability of IL programmes in secondary schools; methods used to impart IL skills to students; the challenges and strategies that could be used to enhance effectiveness of IL programmes in secondary schools to ensure students become lifelong independent learners. The study involved four private secondary schools, namely: Alpha, Loyola, St. Anthony and St. Joseph Secondary schools. The sample was composed of one hundred students, twenty classroom teachers, four head teachers, eight librarians and four heads of the school libraries. A survey method was used in which data were collected using a standardized questionnaire with both closed and open- ended questions which was administered to respondents in, face €“to €“face interviews, data were also collected using Focus Group Discussions and observations. The findings revealed that library orientation is the most popular method used to impart IL skills to students. Factors constraining IL programmes in secondary schools include lack of cooperation between librarians and teachers, inadequate IT facilities, inadequate library skills, lack of awareness on the importance of IL in schools, failure to t integrate IL in the curriculum, poor searching skills, inability of students to evaluate information accessed over the Internet, lack of IL policy, exclusion of IL in the timetable, inadequate librarians and financial constraints. This study recommends cooperation between classroom teachers and library staff in the implementation of IL programmes; improvement of methods of running IL programmes; change of teaching approach in advanced secondary schools and formulation of the IL policy in secondary schools.